A systematic review of genetic variation within nicotinic acetylcholine receptor genes and cigarette smoking cessation. (1st October 2022) - Jones, Stephanie K.; Wolf, Bethany J.; Froeliger, Brett; Wallace, Kristin; Carpenter, Matthew J.; Alberg, Anthony J.
Abstract: Background: Nicotine produces its effects by binding to nicotinic acetylcholine receptors (nAChRs). Variants of genes encoding properties of nAChRs are candidates for affecting likelihood of smoking cessation. Methods: A systematic review was conducted summarizing evidence of associations between single nucleotide polymorphisms (SNPs) of nAChR genes and smoking cessation. From 24 articles meeting inclusion criteria, summary odds ratios (ORs) for associations between nine SNPs and smoking cessation were calculated from 26 studies (N = 233–29, 072) stratified by gene, ancestry, study design, and pharmacotherapy; SNPs in linkage disequilibrium were pooled. Results for a tenth SNP from two GWAS were summarized. Results: People of European ancestry with minor alleles of CHRNA5 rs16969968 and CHRNA3 rs1051730 had longer time to cessation [HR = 0.90, 95 % CI 0.88 – 0.92 (n = 2 studies)] and lower odds of cessation [OR = 0.88, 95 % CI 0.80 – 0.97 (n = 5 cohort studies), OR = 0.64, 95 % CI 0.45 – 0.90 (n = 4 placebo arms)]. Risk of persistent smoking associated with these alleles was attenuated in smokers receiving nicotine replacement therapy (NRT). Recipients of bupropion alone or with NRT with these alleles had higher, though not statistically significant, odds of cessation. Results for CHRNA5 rs588765 and rs680244 were similar to rs16969968/rs1051730 findings. Evidence was limited for other SNPs. Conclusion: Evidence consistently indicates the minor alleles of four SNPs within CHRNA3 or CHRNA5 are risk alleles for cessation failure. Analysis by pharmacotherapy revealed bupropion may be the most efficacious intervention for people with these alleles. Highlights: Nicotinic Acetylcholine Receptors (nAChR) play a role in nicotine addiction. Genes encoding for nAChR subunits are implicated in smoking cessation. Variants of CHRNA5 and CHRNA3 genes are associated with risk of cessation failure. Pharmaceutical interventions mitigate the risk of cessation failure at end of treatment. Long-term studies are need to fully understand genetic risk of persistent smoking.